Effect of perceptions of menstrual blood loss and menstrual pain on women's quality of life. (1st November 2016) - Weisberg, Edith; McGeehan, Kevin; Fraser, Ian S.
Abstract: Objectives: The aim of the study was to explore Australian women's experiences of menstruation and effect on quality of life (QoL). Methods: A representative sample of women recruited through a commercial social research sampling organisation completed a detailed online questionnaire about menstruation. Specific detailed questions were asked about perceptions of heavy menstrual bleeding (HMB) and menstrual pain. Results: The questionnaire was completed by 1575 women aged 20–39 years. Most perceived their bleeding to be light (11.6%) or moderate (60.5%); 363 (22.5%) perceived it to be heavy and 86 (5.3%) very heavy. Women who experienced severe or very severe menstrual pain were significantly more likely to report periods as heavy or very heavy ( p  < .001). The prevalence ratios for being confined to bed during menstruation for women experiencing severe or very severe menstrual pain were 12.02 (95% CI: 5.71–25.31) and 15.93 (95% CI: 7.51–33.78), respectively, compared with women experiencing no pain. The prevalence ratios for being confined to bed were 1.58 (95% CI: 1.11–2.24) and 1.53 (95% CI: 1.04–2.25) for women with heavy or very heavy bleeding, respectively. Women who experienced severe or very severe menstrual pain associated with their HMB were >12 times more likely to be confined to bed for 0.5– 1 day during menstruation than if they reported HMB without pain. Conclusion: Severe menstrual pain with HMB has a much more profound effect on all aspects of women's QoL than HMB alone; it accounts for more days in bed and for loss of productivity.